High-precision radiotherapy for meningiomas: Long-term results and patient-reported outcome (PRO) Hochpräzisionsstrahlentherapie bei Meningeomen: Langzeitergebnisse und patientenberichtete Endpunkte - Kessel, Kerstin A.; Fischer, Hanna; Oechnser, Markus; Zimmer, Claus; Meyer, Bernhard; Combs, Stephanie E. (Strahlentherapie und Onkologie, 2017)
Objective To evaluate long-term outcome after high-precision radiotherapy (RT) of meningioma patients in terms of survival and side effects. Methods We analyzed 275 meningioma cases: 147 lowgrade and 43 high-grade meningiomas (WHO II: n = 40, III: n = 3). In all, 85 patients had no pathologically confirmed histology but were determined as low-grade based on multimodal imaging. Surgery was performed in 183 cases. RT was delivered as either radiosurgery (RS, n = 16), fractionated stereotactic radiotherapy (FSRT, n = 241), or intensity- modulated radiation therapy (IMRT, n = 18). Of 218 patients contacted for patient-reported-outcome (PRO), 207 responded (95%). Results Median follow-up was 7.2 years. For low-grade meningioma the survival rate (OS) was 97% at 3 years, 85% at 10 years, and 64% at 15 years, for atypical meningioma 91% at 3 years, 62% at 10 years, and 50% at 15 years. Local control rate (PFS) for low-grade meningioma was 91% at 3 years, 87% at 5 years, and 86% at 10 years, for atypical cases 67% at 3 years and 55% at 5 years. Of all, 3.0% of patients reported worsened or new symptoms grade ≥3 during RT and the first 6 months thereafter; 17.5% reported a deterioration after more than 2 years. We found the prognostic factors tumor volume and age significantly influencing OS and PFS. Conclusion Complemented by PRO, we found long-term low toxicity rates in addition to excellent local control. Thus, due to the beneficial risk-benefit profile of benign and high-risk meningiomas, RT should be performed as adjuvant treatment and should not be postponed until tumor progression.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Longterm survival; Oncology; Patient-reported outcome (PRO); Radiosurgery; Stereotactic fractionated radiotherapy